Histologic evaluation of bone healing following lowenergy laser irradiation (experimental study (Mustansiria Dental Journal, 2018)
The application of laser is widely used in many branches of medicine and surgery.The high energy laser has coagulating, cauterizing and destructive effect, while thelow energy laser has a bio- stimulating effect.A hole was made using a surgical bur in zygomatic bone of four rabbits and a lowenergy laser was applied on zygomatic bone of experimental group and compared tocontrol non- irradiated group.This study showed that application of low-energy laser has a promoting effect andfacilitate bone deposition in the bony defect of the experimental group whencompared to control group.It may be concluded that application of low-energy laser have promoting effect onacceleration of bone healing.